2014
DOI: 10.1038/gene.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of impairment of normal inflammatory reaction by a high-fat diet

Abstract: The murine dorsal air pouch model is a valuable tool for studying acute peripheral inflammatory reactions. We used this model to study the effect of diet on the onset of acute inflammation. Mice were fed a normal or a high-fat diet (HFD) for 5 weeks. Air pouches were raised and injected with non-stimulating (saline) or stimulating solution (saline containing lipopolysaccharides). After 4 h, leukocytes in the pouch fluid were enumerated, sorted and their viability measured. Cytokine/chemokine levels in the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…1B) . In this model, ~90% of all total leukocytes enumerated in LPS‐injected air pouches, are granulocytes (28). Differential leukocyte counts indicated that LiCl decreased the number of granulocytes migrating into the LPS‐injected pouches by ~40% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) . In this model, ~90% of all total leukocytes enumerated in LPS‐injected air pouches, are granulocytes (28). Differential leukocyte counts indicated that LiCl decreased the number of granulocytes migrating into the LPS‐injected pouches by ~40% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Viability was >85%, as determined by trypan blue dye exclusion. Nearly all (>95%) of the cells migrating into the LPS‐injected pouch were granulocytes (28).…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA transcript level was monitored in mouse dermal fibroblasts using real-time PCR as described by Laflamme et al (2014) . Briefly, reverse transcription was performed using 1 µg of total RNA with a Transcriptor First Strand cDNA Synthesis Kit (Roche Applied Science, Laval, QC, Canada) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary DNA amplifications were performed in a Rotor-Gene Q operated with Q-series software version 2.0.2 (Qiagen Inc., Mississauga, ON, Canada) using 35 cycles of 95 °C for 17 s, 58 °C for 25 s and 72 °C for 25 s. Each reaction mixture contained 40 ng of cDNA, 2 µL of 10× Buffer, 100 µM of dNTPs, 0.1 unit of Taq DNA polymerase (Roche Applied Science) and SYBR Green I (Life Technologies Inc., Burlington, ON, Canada) diluted 1:30,000. For each murine gene of interest, specific primers were designed following certain specifications as described by Laflamme et al (2014) . For the LAMP1 gene, the following primers were used: 5′-ACTGGTAACAACGGAACCTG-3′ (forward) and 5′-ACACATTGGGGTTAGGAACA-3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory neutrophils also produce and release an array of specific soluble mediators of inflammation. Eicosanoids, cytokines, and chemokines [ 6 - 8 ] may each influence the course of immune reactions in a multi-pronged fashion, by soliciting and regulating different cell types involved in the normal development and resolution of an effective inflam-matory response [ 9 ]. Aging reportedly affects important receptor-driven functions of neutrophils [ 10 ].…”
Section: Introductionmentioning
confidence: 99%